A Study on Business Communication on Corporate Social Responsibility in Romania. (2015) - Mihaela, Bucur
Abstract: The paper presents the results of a questionnaire based research conducted on how firms made communication on Corporate Social Responsibility (CSR) in Romania. The objective was to study how communication is performed inside and outside the company. Another objective was to determine how they communicate with the main stakeholders theirs durable development and CSR projects. The research took place between September 2013 and November 2013 and had in view a population of 50 Romanian best companies. A total of 27 enterprises completed questionnaires was obtained and processed. Some of the findings of the research are demonstrate where communication problems are, which components are satisfied through communication and where there should be improvements.